ISO 9001:2015 Quality management: Case study for three-star hotels in Peru (LACCEI, 2024)
Quality Management Systems (QMS) are programs designed to help improve the quality of products and services offered to customers. These programs involve the implementation of procedures and policies in order to meet quality standards and indicators. QMS seek to ensure customer satisfaction, optimize business processes and improve competitiveness. The study was the result of a thesis study, which aimed to determine the measures implemented by three-star category hotels according to the ISO 9001:2015 standard, Trujillo - Peru. The study was descriptive, with a single variable, non-experimental and with a quantitative approach. The technique used was observation, and as an instrument, a known observation guide was used as "Evaluation Diagnosis of the Quality Management System according to NTC ISO 9001-2015", which considered the levels: Fully complies, partially complies, complies with the minimum of the stated criterion and does not comply with the stated criterion (not established, not implemented, not maintained). The dimensions evaluated were: Organization context, leadership, planning, support, operation, performance evaluation and improvement. It was determined that the level of implementation was "partial compliance" (55.1%) for "Hotel 1" and "minimally complied" (37.3%) for "Hotel 2". The main limitation was the scarce scientific literature in the hotel sector in the presentation of a scientific article.